2022
DOI: 10.3389/fphys.2022.927819
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Viscous Guar Gums on Growth, Apparent Nutrient Digestibility, Intestinal Development and Morphology in Juvenile Largemouth Bass, Micropterus salmoides

Abstract: An 8-week feeding trial was conducted to investigate the effects of different viscous guar gums on the growth performance, apparent nutrient digestibility, intestinal development and morphology of juvenile largemouth bass. Four isoproteic and isolipidic diets (crude protein 42.5%, crude lipid 13.7%) were formulated to contain 8% cellulose (Control group), 8% low viscous guar gum with 2,500 mPa s (Lvs-GG group), 8% medium viscous guar gum with 5,200 mPa s (Mvs-GG group) and 8% high viscous guar gum with 6,000 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…BUN is the end product of amino acid catabolism in fish, while AST is an amino acid metabolizing enzyme distributed in the liver and released into the blood when liver cells are damaged [ 1 ]. Therefore, an increase in these parameters suggests that dietary SNSP promotes proteolytic metabolism and induces liver damage [ 41 , 42 , 43 ]. Similarly, our previous studies also showed that dietary SNSP induces liver damage in rainbow trout and largemouth bass ( Micropterus salmoides ) [ 1 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BUN is the end product of amino acid catabolism in fish, while AST is an amino acid metabolizing enzyme distributed in the liver and released into the blood when liver cells are damaged [ 1 ]. Therefore, an increase in these parameters suggests that dietary SNSP promotes proteolytic metabolism and induces liver damage [ 41 , 42 , 43 ]. Similarly, our previous studies also showed that dietary SNSP induces liver damage in rainbow trout and largemouth bass ( Micropterus salmoides ) [ 1 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an increase in these parameters suggests that dietary SNSP promotes proteolytic metabolism and induces liver damage [ 41 , 42 , 43 ]. Similarly, our previous studies also showed that dietary SNSP induces liver damage in rainbow trout and largemouth bass ( Micropterus salmoides ) [ 1 , 41 ]. This evidence suggests that dietary SNSP is the main type of NSPs causing liver damage in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Four practical diets containing 8% microcrystalline cellulose (MC) and carboxymethyl cellulose (CMC) of 2,500, 5,000, and 6,500 mPa s [hereinafter MC, low-viscosity CMC (Lvs-CMC), medium-viscosity CMC (Mvs-CMC), and high-viscosity CMC (Hvs-CMC) groups, respectively] were designed (values in millipascal second denote the dynamic viscosity, which represents the internal friction force generated by the interaction of fluids between two 1-m 2 flat plates with a distance of 1 m when they move relative to each other at a speed of 1 m/s). The control group data have been published in a previous study (Liu et al, 2022b). All materials were first finely milled into powder, mixed thoroughly after being screened using a 0.30-mm diameter mesh, and then accurately weighed.…”
Section: Feed Preparationmentioning
confidence: 99%
“…The visceral mass, gut, and liver were weighed accurately and the intestinal length measured. Another group of fish (n = 4 from each cage) was randomly selected for the collection of blood samples according to the method described by Liu et al (2022b). The proximal and distal intestines of two fish from each cage were collected into separate Eppendorf (EP) tubes and stored at −80°C for subsequent analysis.…”
Section: Sampling Strategymentioning
confidence: 99%
See 1 more Smart Citation